Miltefosine in the treatment of cutaneous leishmaniasis caused by Leishmania braziliensis in Brazil: a randomized and controlled trial. - Paulo R Machado; Julia Ampuero; Luiz H Guimarães; Leonardo Villasboas; Ana T Rocha; Albert Schriefer; Rosana S Sousa; Anette Talhari; Gerson Penna; Edgar M Carvalho (PLoS Neglected Tropical Diseases, 2010)
Background Cutaneous leishmaniasis (CL) is treated with parenteral drugs for decades with decreasing rate cures. Miltefosine is an oral medication with anti-leishmania activity and may increase the cure rates and improve compliance. Methodology/principal findings This study is a randomized, open-label, controlled clinical trial aimed to evaluate the efficacy and safety of miltefosine versus pentavalent antimony (Sb(v)) in the treatment of patients with CL caused by Leishmania braziliensis in Bahia, Brazil. A total of 90 patients were enrolled in the trial; 60 were assigned to receive miltefosine and 30 to receive Sb(v). Six months after treatment, in the intention-to-treat analyses, the definitive cure rate was 53.3% in the Sb(v) group and 75% in the miltefosine group (difference of 21.7%, 95% CI 0.08% to 42.7%, p = 0.04). Miltefosine was more effective than Sb(v) in the age group of 13-65 years-old compared to 2-12 years-old group (78.9% versus 45% p = 0.02; 68.2% versus 70% p = 1.0, respectively). The incidence of adverse events was similar in the Sb(v) and miltefosine groups (76.7% vs. 78.3%). Vomiting (41.7%), nausea (40%), and abdominal pain (23.3%) were significantly more frequent in the miltefosine group while arthralgias (20.7%), mialgias (20.7%) and fever (23.3%) were significantly more frequent in the Sb(v) group. Conclusions This study demonstrates that miltefosine therapy is more effective than standard Sb(v) and safe for the treatment of CL caused by Leishmania braziliensis in Bahia, Brazil. Trial registration Clinicaltrials.gov Identifier NCT00600548.